Droplet digital PCR as alternative to microbiological culture for Mycobacterium tuberculosis complex detection in bovine lymph node tissue samples - Sánchez-Carvajal, José María; Vera-Salmoral, Eduardo; Huerta, Belén; Galán-Relaño, Ángela; Ruedas-Torres, Inés; Larenas-Muñoz, Fernanda; Luque, Inmaculada; Carrasco, Librado; Gómez-Laguna, Jaime (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Bovine tuberculosis (bTB) caused by Mycobacterium tuberculosis complex (MTC) remains a significant concern for public health. Direct real-time PCR and droplet digital PCR (ddPCR) are proposed as alternative tools to enhance diagnostic precision and efficiency. This study aims to assess the diagnostic performance of a ddPCR assay targeting IS6110 for the detection of MTC DNA in both microbiological culture and fresh lymph node (LN) tissue samples obtained from cattle, in comparison with the established reference standard, the microbiological culture followed by real-time PCR. Methods The fresh LNs (N=100) were collected each from a different cattle carcass at the slaughterhouse. The limit of detection of ddPCR-IS6110 was set to 101 copies per 20 μl reaction. Results DdPCR-IS6110 detected 44 out of 49 reference-standard positive samples and yielded negative results in 47 out of 51 reference-standard negative samples, resulting in adjusted sensitivity (Se) and specificity (Sp) of 90.76% [95% confidence interval (CI): 82.58 - 98.96%)], and 100% (95% CI: 100%) respectively. The estimated adjusted false negative rate (FNR) was 9.23% (95% CI: 1.04 - 17.42%) and the false positive rate (FPR) was 0% (95% CI: 0%). When directly applied from fresh bovine LN tissues, ddPCR-IS6110 identified 47 out of 49 reference-standard positive samples as ddPCR-IS6110-positive and 42 out of 51 reference-standard negative samples as ddPCR-IS6110-negative, resulting in adjusted Se and Sp values of 94.80% [95% (CI): 88.52 - 100%] and 100% (95% CI: 100%), respectively. The adjusted FNR was 5.20% (95% CI: 0 - 11.50%) and the FPR was 0% (95% CI: 0%). Noteworthy, ddPCR-IS6110 disclosed as positive 9 samples negative to reference-standard. Discussion DdPCR-IS6110 proved to be a rapid, highly sensitive, and specific diagnostic tool as an alternative to reference-standard method.